Ismail Gasprinski and the idea of Alash (Eurasian Journal of Philology Science and Education, 2022)
In the middle of the 19th century, the Muslim countries that were under the colonialism of the Russian Empire were on the verge of extinction as a nation. At this historical moment, representatives of the intellectuals of the Crimean and Kazan Tatars made efforts to develop national spirituality, as a result, the «era of national awakening» began. At its origins stood the educator, politician, journalist, reformer, teacher and most importantly, the founder of «Jadidism» Ismail Gasprinski. Crimean Tatar scientist Ismail Gasprinski made a great contribution to the education of the Tatar people. In addition to publishing in the Tatar language in newspapers and magazines on national and religious issues, he invented the method of mass literacy «usul-i jadid». He also wrote and invented textbooks and manuals for Tatar schoolchildren. At the same time, he taught people to read and write in a new way, who previously considered knowledge only to memorize the words of the Koran. The elimination of the illiteracy of the people was a common problem not only for the Tatar people, but also for all Russian Muslims of that time. At the end of the 19th and the beginning of the 20th centuries, the movement «Jadidism» (a new method of teaching) came to Kazakhstan. The Alash intellectuals used the «Jadid» method to write textbooks in various fields of science. The press covered various issues of science-education, culture, literature of the people of that time, which led to a great movement in the Kazakh society.